(untitled) (VETERINARIA, 2020)
The study was aimed at determining levels of alanin aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) in the plasma of 229 dairy Holstein-Friesian breed cows in different stages of the re¬production cycle and regarding the seasonal changes (diet conditions). Cows were divided into the groups: lactation (Group A), postpartal period within 15 days from calving (Group B) and dry period (Group C). Seasonal variations affected AST activity within Groups A and B, while Group C showed no seasonal influence. Differences between Groups A and B were determined during winter, as well as among Groups A and C during the same season. The highest activity of ALT was measured in cows from Group A during the winter season. ALP activity showed no statistical difference among groups, though statistical significance was noted within seasonal changes. The activity of LDH showed no statistical significance within Group C with regard to the seasonal changes. Statistically significant difference was found between cows of Group A and C during the winter season. Differences were considered statistically significant when p<0,05. Research results showed a significant influence of milk production and dry period on the activities of measured enzymes in the blood plasma so we can conclude that there is a need for constant monitoring of the described parameters during the production period.